Accelerating agricultural technology adoption: Validating recent research insights with research partners in Kenya - Kramer, Berber; Kilonzi, Emily (International Food Policy Research Institute, 2024)
This report explores the accelerating adoption of agricultural technologies in Kenya, focusing on the validation of recent research insights through collaboration with local research partners. With agriculture being a key sector in Kenya's economy, the adoption of innovative agricultural practices and technologies is crucial to enhancing productivity, sustainability, and food security. The study highlights key findings from recent research on barriers to technology adoption, including financial constraints, knowledge gaps, and infrastructure limitations. By engaging with Kenyan agricultural researchers and practitioners, the report identifies strategies to address these barriers, facilitate broader adoption of technology, and improve the livelihoods of smallholder farmers. Insights from this collaboration are essential for informing policy decisions and supporting programs aimed at fostering sustainable agricultural development in the region.